Integrated multicomponent analysis based on UHPLC‐Q‐Exactive Orbitrap‐MS and network pharmacology to elucidate the potential mechanism of Baoyuan decoction against idiopathic pulmonary fibrosis. Issue 5 (9th April 2022) - Zhang, Binbin; Gao, Dongyang; Xu, Gonghao; Zhu, Wenxiang; Liu, Jing; Sun, Rui; Wang, Lu; Zhang, Chen; Ding, Qi; Shi, Yuanyuan
Abstract: Introduction: Idiopathic pulmonary fibrosis (IPF) is a serious lung disease with a high mortality rate. Baoyuan decoction (BYD), a classic medicinal food homology recipe, has anti‐apoptotic effects, enhances immune function, and alleviates fibrosis, suggesting that it may be a potential therapeutic drug for IPF. Objectives: We aimed to identify the main active ingredients of BYD, determine the basis of its efficacy, prove its anti‐IPF effects, and explore the mechanisms underlying its anti‐IPF effects. Materials and methods: In this study, the active components of BYD were detected and analysed by ultra‐high‐performance liquid chromatography coupled with hybrid quadrupole Orbitrap mass spectrometry (UHPLC‐Q‐Exactive Orbitrap‐MS). A network pharmacology analysis was performed to determine the potential targets and relevant pathways of BYD in treating IPF. Western blotting and quantitative real‐time polymerase chain reaction (qPCR) were conducted to verify the efficacy of BYD against IPF. Finally, molecular docking and qPCR were performed to identify the central targets of BYD. Results: A total of 39 components of BYD were identified. After performing the network pharmacology analysis, 35 active components and eight presumptive targets of BYD were found to play a central role in its anti‐IPF effects. The molecular docking results indicated that most of the active components of BYD exhibited good binding activity with these eight central target proteins. In addition, the expression of collagen, α‐SMA, and these eight targets in human pulmonary fibroblast (HPF) cells was suppressed from treatment with BYD. Conclusion: This study determined the efficacy of BYD against IPF and clarified its multiple‐target and multiple‐pathway mechanisms. Furthermore, the study also provides a new method for exploring the chemical and pharmacological bases of other traditional Chinese medicine (TCM). Abstract : Baoyuan decoction (BYD) may be an effective drug for treating Idiopathic pulmonary fibrosis (IPF). We used UHPLC‐Q‐Exactive Orbitrap‐MS to identify the main ingredients of BYD and used network pharmacology and in vitro experiments to prove the anti‐IPF effect of BYD and explore the underlying mechanism by which it exerts this effect. The results showed that BYD treatment for IPF works through multiple components, targets, and pathways and that these pathways may produce better therapeutic effects through synergistic treatment.